Experimental study of an organic Rankine cycle system with radial inflow turbine and R123 - Shao, Long; Zhu, Jie; Meng, Xiangrui; Wei, Xinli; Ma, Xinling (Elsevier, 2017)
A new micro radial inflow turbine is developed fora mini organic Rankine cycle (ORC) system in this study. With R123 as the working fluid, the turbine operational characteristics and performance are investigated by experiments. Based on the experimental data, the maximum rotational speed of the radial inflow turbine reaches53564r/min, and the maximum output power of the turbine is3.386kW and the maximum electric power reaches1.884kW. When the turbine rotational speed is34586r/min, the system isentropic and electromechanical efficiencies achieve the maximum values of 83.6% and65.3% respectively. Both the turbine isentropic and thermal efficiencies increase with the heat source temperature.